(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This study leverages q-calculus to establish q-Hermite-Hadamard type inequalities for strongly convex functions, showcasing possible extensions of well-known results in the field. Additionally, it enhances these findings by exploring the strong convexity of the function Φ. Furthermore, the q-midpoint and q-trapezoidal inequalities are unified within a comprehensive framework. Ultimately, the results suggest that the newly derived inequalities can be effectively applied in the context of special means.